Preparation of novel biodegradable ropivacaine microspheres and evaluation of their efficacy in sciatic nerve block in mice - Ni Q; Chen WR; Tong L; Cao J; Ji C (Dove Medical Press, 2016)
Qiang Ni, Wurong Chen, Lei Tong, Jue Cao, Chao Ji Department of Anesthesiology, Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China Abstract: In this study, ropivacaine chitosan-loaded microspheres for subcutaneous administration were developed. The systems were characterized in terms of surface morphology, particle size, encapsulation efficiency, and in vitro release behavior. Results showed that the microspheres had drug loading rate of 7.3% and encapsulation efficiency of 91.2%, and their average diameter was 2.62±0.76 µm. The morphology study revealed that the microspheres are uniform monodispersed spheres and did not form aggregates in aqueous solution. It was clearly observed that the release profile of ropivacaine microspheres exhibited a biphasic pattern: the initial burst release within the first 2 hours and a following slower and sustained release over a long time. In vivo, a greater area under the plasma concentration–time curve from 0 to t (AUC0–t) was obtained from the microspheres (4.27-fold), than from the injection group, which indicated that there was a significantly improved systemic exposure to ropivacaine. Pharmacodynamics result showed that preparing ropivacaine as microsphere preparation could not only extend the drug effect time but also decrease the administration dosage. Keywords: ropivacaine, chitosan, microspheres, in vitro release, pharmacodynamics